Microleakage of two resin composites by using different light curing systems (Mustansiria Dental Journal, 2024)
This study was conducted to evaluate marginal microleakage of two resineomposite (Glacier resin composite and Filtek P 60 resin composite) either cured witheonventional light cure unit ( Astralis 5) or light emitting diodes (LED) light cure unit»Radii). Forty class V cavities were prepared in 20 extracted second premolars, onebuccaly and one palataly in each tooth. Each cavity was located lmm coronal toeementoenamel junction and lmm apical to it. The teeth were randomly divided into 4groups, each group of five teeth (I0 cavities): Group I was filled with Glacier resincomposite and cured with LED curing unit. Group ll filled with Glacier and curedin ith Astralis 5 curing unit. Group lll filled with Filtek P60 resin composite and curedv- ith LED curing unit. Group IV filled with Filtek P 60 and cured with Astralis curingxnit. The teeth were stored in distilled water for seven days. Then the apices of theteeth were sealed with sticky wax and the teeth were covered with two layers of nailvamish except lmm around the restoration. The teeth were immersed in 0.5% basicfaehsin dye for 24 hours at 37°C in the incubator and then were longitudinallyxctioned in a buccolingual direction and the extent of dye penetration was recorded.The statistical analysis of the result revealed that the use of LED light cure unit,results in highly significant reduction in the microleakage occlusally and gingivally